Violence in the North West with special reference to Liverpool and Manchester 1850-1914 - Orr, David (UK Data Service, 2002)
The project was intended to investigate all forms of interpersonal violence, from common assault to murder, in the second half of the 19th century, and to attempt to differentiate and contextualise the range of violent offences. The aims of the project were to: 1. Expand and enhance historical understanding and knowledge of violence in the second half of the nineteenth century; 2. Examine critically the accepted interpretation that there was a long-term decline in violence, placing special emphasis on the 1870s as a possible 'watershed' decade; 3. Examine, where possible, under-reported crimes of violence directed at women and children; 4. Examine contemporary reactions to and perceptions of violence; 5. Provide the first full historical study of all types of violent crime which offers depth and context to studies of crime in the late twentieth century.